William John Burchell, multi-skilled polymath: his return journey from Graaf Reinet to Uitenhage 1813 - Stewart, Roger (Toposcope, 2021)
Two hundred and ten years ago, 29-year-old William John Burchell stepped on to the wooden jetty near Cape Town’s Castle and immediately started planning his journey of scientific exploration of southern Africa. This would take four years, mostly by ox-wagon, and cover 7000km. On 19 June 1811, he departed Cape Town ’’with a mind free from prejudice’’ and “solely for the purpose of acquiring knowledge” …He travelled to about 150 km north of Kuruman, explored the Ky-Gariep (Vaal) River and returned to Cape Town via Graaff-Reinet, the mouth of the Great Fish River, Uitenhage, Mossel Bay and Swellendam...